Analysis of Waste Material Using Lean Construction and Fault Tree Analysis Approaches - Sapna Rezain Kaca Sungkana; Anik Ratnaningsih; Krisnamurti Krisnamurti (Eduvest - Journal of Universal Studies, 2026)
This research analyzes waste material in construction projects using Lean Construction and Fault Tree Analysis approaches. The study was conducted on three building projects: Building X in Makassar, Building Y in Batam, and Building Z in Kediri. The objectives are to estimate waste cost from material waste during structural and architectural work, identify the highest waste material indicators, and determine optimization strategies to improve waste cost efficiency. The Waste Assessment Model method was used to identify waste variables, while Fault Tree Analysis was employed to determine root causes and calculate the probability of waste occurrence. Data collection was conducted through direct field observations, interviews with contractors, and questionnaires. Results showed that waste costs in Building X project amounted to Rp. 1,371,690,630 (4.93% of contract value), Building Y project Rp. 1,434,910,750 (3.75% of contract value), and Building Z project Rp. 1,573,029,639 (3.36% of contract value). Waste Assessment Model analysis revealed three critical waste types across all projects: Defects (19.95-20.09%), Overproduction (18.19-18.32%), and Inventory (16.16-16.27%). Fault Tree Analysis identified that the highest probability variable causing waste material was A1 "Human or Group Failure" (0.6066-0.6565), while the lowest was C2 "Storage Capacity and Method" (0.3040-0.3623). This research provides strategies for waste cost efficiency through identification of dominant causes and probability calculations of waste occurrence.